Perception of the educational academic motivation and academic performance in sixth primary students of a Lima district - Grajeda Montalvo, Alex (2019)
The study seeks to determine the relation of academic motivation applied by teacher and academic performance in students from sixth grade of elementary level. For the study of the first variable was applied Teaching Motivation questionnaire of Patiño, Laura & Rado (2009) to 275 male and female students in elementary sixth grade from Surco district in order to assess the perception that students have with respect to the motivation that exert their teachers. Likewise, we collected the notes obtained by the students at the conclusion of the second bimester. It was found that the academic motivation is of a higher level and the academic performance is the level of achievement (A).Only found significant differences according to the type of educational institution on academic performance. There were no significant differences according to sex and age and therefore correlations are made with the total sample. No correlations were found between motivation academic teaching and academic performance in sixth grade pupils of the elementary from Surco district.